High-Dose Estradiol-Replacement Therapy Enhances the Renal Vascular Response to Angiotensin II via an AT2-Receptor Dependent Mechanism - Tahereh Safari; Mehdi Nematbakhsh; Roger G. Evans; Kate M. Denton (Hindawi Limited, 2015)
Physiological levels of estrogen appear to enhance angiotensin type 2 receptor- (AT2R-) mediated vasodilatation. However, the effects of supraphysiological levels of estrogen, analogous to those achieved with high-dose estrogen replacement therapy in postmenopausal women, remain unknown. Therefore, we pretreated ovariectomized rats with a relatively high dose of estrogen (0.5 mg/kg/week) for two weeks. Subsequently, renal hemodynamic responses to intravenous angiotensin II (Ang II, 30-300 ng/kg/min) were tested under anesthesia, while renal perfusion pressure was held constant. The role of AT2R was examined by pretreating groups of rats with PD123319 or its vehicle. Renal blood flow (RBF) decreased in a dose-related manner in response to Ang II. Responses to Ang II were enhanced by pretreatment with estradiol. For example, at 300 ng kg−1 min−1, Ang II reduced RBF by 45.7±1.9% in estradiol-treated rats but only by 27.3±5.1% in vehicle-treated rats. Pretreatment with PD123319 blunted the response of RBF to Ang II in estradiol-treated rats, so that reductions in RBF were similar to those in rats not treated with estradiol. We conclude that supraphysiological levels of estrogen promote AT2R-mediated renal vasoconstriction. This mechanism could potentially contribute to the increased risk of cardiovascular disease associated with hormone replacement therapy using high-dose estrogen.